FOC of SRM using More Efficient DC-DC Converter Topology - Emad S. Abdel-Aliem (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
Numerous studies had been made to improve the switched reluctance motor operation depend on the modification of the machine design, proposing the converter designs and/or applying a suitable control method. This paper introduces the field orientation control method for that motor using a simple and very efficient DC-DC converter topology. This control method is presented by two techniques; first technique is the advance of the turn-on switching angle and the other technique is the retard/delay of the turn-off switching angle. Instantaneous and average motor characteristics are obtained using Matlab/Simulink software package. Comparison between the simulation results presented using two converter types. A precise speed and torque control are obtained. The average total torque per current is maximized.